Inverse Correlation Between Distress and Performance in the Medical Rescuers Against COVID-19 in Wuhan - Xie, Fang; Wang, Xue; Zhao, Yun; Wang, Shi Da; Xue, Cong; Wang, Xiao Tian; Chen, Yu Xin; Qian, Ling Jia (Frontiers in Psychiatry, 2021)
Background: During the COVID-19 pandemic, the Chinese government had transferred many medical rescuers to Wuhan, which provided effective support in disease control. The high-intensity working and mental stress during rescue could induce distress and negatively impact the performance of rescuer afterward. Materials and Methods: To identify the characteristics of stress load and its possible effects on performance, the study surveyed 90 medical rescuers in Wuhan using a mobile phone–based self-rated questionnaire. Results: The results showed an existence of universal but mostly mild distress in rescuers. About 95.6% of the participants reported that they had at least one symptom of distress, whereas, the median scores were <30 (100 as max). Compared with civilian rescuers, a higher proportion of working with immediate virus contact was found in military medical rescuers (P = 0.008); however, no statistical differences of stress load were found between civilians and militaries. The rescuers with positive cognition or good psychological preparation were found having lower stress loads than other rescuers. An inverse correlation between the stress load and performance (R = −0.24, P = 0.023) and a positive correlation between social support and working performance (R = 0.349, P = 0.001) were found in our survey, suggesting the possible negative effects of stress and the beneficial effects of social support on performance. Conclusion: Our study indicated that more attention should be paid to the distress of medical rescuers against COVID-19. Positive cognitions, good psychological preparations, and sufficient social support would be necessary to reduce the distress and improve the performance in COVID-19 rescue.